Primary healthcare practitioners and patient blood management in Africa in the time of coronavirus disease 2019: Safeguarding the blood supply - Claire L. Barrett (AOSIS, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has highlighted various weaknesses in global healthcare services. The blood supply in Africa is a critical element of the healthcare service that may be significantly affected by the pandemic. By implementing principles of patient blood management, primary healthcare practitioners may play an important role in the resilience of the blood supply during the COVID-19 pandemic.